Recent Trend of Population Policies in Iraq - Salih, Enas Muhammad (Al-Adab Journal, 2022)
This resulted from the traditional population policies adopted by Iraq for many decades, which took care of the (quantum) population aspect as a result of the political and economic conditions in which it was living, represented by the comprehensive development process that it had planned since the middle of twentieth century, in addition to its two wars a bitter experience of economic siege during the last two decades of the century. in the past, all of this called for Iraq to adopt a population policy that deals with the population size and encourages birth openly and seeks to do so according to its legislative authority and planned programs. which later resulted in the presence of a tide of youth that the subsequent economic conditions of Iraq, since the beginning of the twenty – first century, have failed to meet the requirement of absorbing this squandered abundance due to the conditions of the American occupation and the successive political and economic setbacks it is experiencing. the matter is getting worse as the demographic gift is approaching, and there are no signs, indicators or opportunities that indicate Iraq s readiness to receive this expected gift. therefore, the imperative duty is to adopt an emergency (immediate) population policy that stems from sound, scientific and well – studied foundations that are concerned with the population (type) side.